IMPROVING ABILITY WRITING AROUND DESCRIPTION WITH THE STUDENT'S FIELD TRIP METHOD - m Nurzin R Kasau; Darmi Darmi; M Hijaz Tahir (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2023)
The low Skills write essay description caused by several factors, namely: 1) less students understand the essence of descriptive essay; 2) student Not yet describe object which is clear with involve impression sense;students have not been able to use the structure good and correct language; 4) students have not used capital letters correctly; 5) students have difficulty expressing ideas. Study This aim describe Enhancement Ability Write Essay Description with Field Trip Method Grade IV students at SDN 2 Rappang, Pancarijang District, Sidrap Regency . Study This use method study action class (PTK). subject this study were fourth grade students of SDN 2 Rappang, Pancarijang, Sidrap, while the object writes a descriptive essay using the field trip method. Technique collection data Which used is observation And test ability student. This study uses a qualitative descriptive analysis technique. From the results research can be concluded that the field trip method can improve ability write essay description student on cycle I after apply the field trip method of students who scored > 70 as many as 6 students with an average score class average of 65.93. After being given action cycle II students who scored> 70 as much 14 students with an average value as much 77,26.